PERSEPSI ORANGTUA PEKERJA BANGUNAN TENTANG PENDIDIKAN ANAK DI KELURAHAN BANJAR SERASAN KECAMATAN PONTIANAK TIMUR - Helisa, Helisa; Rustiyarso, Rustiyarso; Supriadi, Supriadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis Thesis entitled ?Construction working parents perception towards children education in Kelurahan Banjar Serasan Kecamatan Pontianak Timur?. The purpose of this research is to describe the children level of education, also to analyze the construction working family. The approach used in this research is a qualitative approach in form of descriptive with purposive sampling method and snowball sampling. The technique of data collection used is interview and documentation technique. The total of informants in this research is six persons, consist of three construction working parents, three children with lack of educations. The result of this research proves that the contruction working family in Kelurahan Banjar Serasan Kecamatan Pontianak Timur still have a neutral perception toward children education that some parents think education is important and beneficial and some parents also think education is expensive and indifferent. Moreover, there are some causes of children?s lack of education, those are: children?s lack of interests, lack of desire/expectations, lack of encouragement/motivation, parents? educations background, parents? concern, and family?s economical weakness. Keyword: Parents Perception, Contruction Worker, Children Education.